Violence, struggle and resistance: historicity of rural education to indigenous school education - Leni Barbosa Feitosa; Idemar Vizolli (Universidade Federal do Norte do Tocantins, 2019)
This article aims to identify, through the historicity of the school offered to indigenous peoples, the perspective of rural education, vehemently pursued, guided to indigenous school education and how their own ways of thinking, producing and expressing knowledge that emanate from their cultures were legitimized and valued in the school environment, in the light of a literature review and documentary analysis. The sidewalk of the educational prospects has undergone a historicity evidenced by the violence of the Eurocentric cultural imposition when envisaging that the threshold of the school supply to the indigenous peoples interweaved strategic arrangements of the European invaders to make them useful to the country; and struggle and resistance of the indigenous peoples to re-signify in the school environment the process of teaching and learning in their territories, aligning them with the traditional education of their people. The category of indigenous school was legitimized only from the recognition of social organization, customs, languages, beliefs and traditions, instituted by the Federal Constitution of 1988 and made official in 1999 through Opinion n° 14/1999 and Resolution n° 03/1999. It is important to note that the advent of indigenous school education results not from the well-being of the State to indigenous peoples, but from their struggle and resistance to numerous cultural impositions.